Antike und Identität: die Herausforderungen der Altertumswissenschaften - Grethlein, Jonas (Mohr Siebeck, 2022)
"What is the significance of antiquity today? Does it contain the roots of our cultural identity or do Classical Studies have to be overhauled in the light of today's identity politics? Jonas Grethlein, Professor of Greek at Heidelberg University, shows the pitfalls of the concept of identity on both sides and reflects on how Greek and Roman antiquity can be made fruitful for the present."--From publisher's website